Leucine-enriched essential amino acid supplementation in mechanically ventilated trauma patients – a feasibility study - Wandrag,L; Brett,SJ; Frost,G; To,M; Loubo,E; Jackson,N; Umpleby,M; Bountziouka,V; Hickson,M (Trials, 2019)
Background: Critically ill patients lose up to 2% muscle mass per day. We assessed the feasibility of administering a leucine-enriched essential amino acid (L-EAA) supplement to mechanically ventilated trauma patients with the aim of assessing the effect on skeletal muscle mass and function. Methods: A randomised feasibility study was performed over 6 months in intensive care (ICU), patients received 5g L-EAA five times per day in addition to standard feed (L-EAA group) or standard feed only (control group) up to 14 days. CRP, albumin, IL-6, IL-10, urinary 3-MH, nitrogen balance, protein turnover ([1-13C] leucine infusion), muscle depth change (ultrasound), functional change (Katz & Barthel indices) and muscle strength Medical Research Council (MRC) sum score to assess ICU Acquired Weakness, were measured sequentially.Results: Eight patients (9.5% of screened patients) were recruited over 6 months. L-EAA doses were provided on 91/124 (73%) occasions. Inflammatory and urinary marker data were collected; serial muscle depth measurements were lacking due to short length of stay. Protein turnover studies were performed on five occasions. MRC-sum score could not be performed as patients were not able to respond to the screening questions. The Katz & Barthel indices did not change. L-EAA delivery was achievable, but meaningful functional and muscle mass outcome measures require careful consideration in the design of a future RCT. Conclusion: L-EAA was practical to provide, but we found significant barriers to recruitment and measurement of the chosen outcomes which would need to be addressed in the design of a future, large randomised controlled trial.